Algorithmic Ulama: Generative AI, Religious Authority, and the Reconfiguration of Da'wah Communication Ethics in Indonesian Islam - Nur Fatimah; Murjazin; Muhammad Abdul Kharis (LaKaspia, 2026)
Objective: This study aims to examine how generative artificial intelligence (AI) is transforming religious authority and da’wah (Islamic propagation) communication ethics in Indonesia, the country with the world’s largest Muslim population. Specifically, it seeks to analyze the implications of AI for the production, circulation, and legitimacy of religious knowledge and guidance within the Indonesian Islamic public sphere. Method: The study employed a systematic literature review (SLR) guided by the PRISMA 2020 protocol. Forty peer-reviewed and Scopus-indexed sources published predominantly between 2021 and 2026 were analyzed using thematic synthesis. The review focused on five analytical domains: institutional AI adoption within Nahdlatul Ulama and Muhammadiyah, the epistemic reliability of AI-generated religious guidance, algorithmic mediation and fragmentation of religious authority, ethical tensions in AI-mediated da’wah communication, and comparative global perspectives on digital Islamic authority. Results: The findings indicate that generative AI simultaneously functions as an enabling and destabilizing force in Indonesian Islamic communication. On the one hand, AI enhances the reach, personalization, and efficiency of da’wah communication. On the other hand, it destabilizes the traditional isnad-based model of religious legitimacy, introduces risks of misattribution and doctrinal oversimplification, and creates new forms of algorithmically mediated religious influence operating outside conventional institutional accountability structures. The study further identifies a significant asymmetry between the rapid pace of AI adoption and the comparatively slow development of ethical and regulatory frameworks governing AI-mediated religious communication. Conclusion: This study proposes the concept of the algorithmic ulama to describe the emerging hybrid configuration of human and machinic religious authority, and develops a preliminary ethical framework for AI-mediated da’wah grounded in Islamic communication ethics (akhlaq al-i‘lam) and mediatization theory. It contributes a theoretically integrated, context-specific account of AI’s implications for Islamic communication scholarship and offers practical recommendations for religious institutions, media regulators, and communication educators in Indonesia.